The Effectiveness of the hybrid problem-based learning approach in training of speaking English at SMAN 14 Makassar - Alunandika, Nurul Khalifah; AM, St. Asmayanti; Hafid , Hilda (Journal of Language Testing and Assessment, 2023)
This study aims to see the effectiveness of the hybrid problem-based learning approach in training of speaking English at SMAN 14 Makassar. The researcher used quantitative research with a pre-experimental where the data gained from speaking test and data was collected through pre-test, treatment and post-test. The population of the research was the member of OSIS SMAN 14 Makassar. The total of population were 28 students.The result showed that the improvement of students’ accuracy and fluency from 28 students. The mean score of accuracy in post-test showed (75,5) that is higher than pre-test (54,3), with percentage of improvement (39%). Besides, most of students got very good score (71-85). Furthermore, the t-test value (2.0) that is greater than t-table value (2.052). It was concluded that there was significant improvement in accuracy by implementing the hybrid problem-based learning. Then, the mean score of fluency in post-test showed (64,4) that is higher than pre-test (46,1), with percentage of improvement (39%). Besides, most of students got good score (56-70). While, the t-test analysis of fluency showed (1.8) that is greater than t-table (2.052). It was concluded that there was significant improvement in fluency by implementing the hybrid problem-based learning.Based on the findings, it can be concluded that the hybrid problem-based learning was effective to improve the students speaking skills approach in training of speaking English at SMAN 14 Makassar.